Solid material with open multiple porosity comprising geopolymer and solid particles and method for preparing the same

By using a combination of micropore-mesporous geological polymers and different particles, a material with high mechanical strength and open multiple pores was prepared, which solved the problem of insufficient openness of the material pore structure in the prior art, and improved the contact efficiency between the fluid and the particles and the purification ability of the material.

CN115379891BActive Publication Date: 2025-04-29COMMISSARIAT A LENERGIE ATOMIQUE ET AUX ENERGIES ALTERNATIVES +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202180011035.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-28
Filing Date
2021-01-25
Publication Date
2025-04-29
Estimated Expiration
2041-01-25

AI Technical Summary

Technical Problem

The prior art is difficult to prepare materials with high mechanical strength and multiple interconnected pores, especially in the case of active particles, the pore structure of the material is not open enough, making it difficult for fluids to contact the particles.

Method used

A combination of a mineral inorganic matrix made of microporous-mesporous geological polymer and solid compound particles different from the geological polymer was prepared by an oil-in-water emulsion method to form a material with open macroporous.

Benefits of technology

The high mechanical strength and open multi-pore structure of the material are achieved, allowing the fluid to contact the particles more easily, and the transportability and purification efficiency of the material in the fixed bed method are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115379891B_ABST
    Figure CN115379891B_ABST
Patent Text Reader

Abstract

A solid material with open, multiple and at least partially interconnected pores, the solid material comprising an inorganic matrix formed of a microporous-mesoporous geopolymer and particles of at least one solid compound different from the geopolymer, the inorganic matrix having at least partially interconnected open macropores surrounded by sides or walls formed of the microporous-mesoporous geopolymer, the particles being distributed in the macropores and / or in the sides or walls. A method for preparing the material. A method for separating at least one metal cation or metalloid cation from a liquid medium containing the same, wherein the liquid medium is contacted with the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid material having open multiple porosity, also referred to as a material having hierarchical open porosity, comprising a geopolymer and solid particles distributed in the pores.

[0002] More specifically, the present invention relates to a solid material with open multiple porosity, comprising a mineral inorganic matrix made of a microporous-mesoporous geopolymer and particles of at least one solid compound different, distinct and phase-separated from the geopolymer, in which the mineral inorganic matrix has at least partially interconnected open macropores, which are bounded by sides or walls formed by the microporous-mesoporous inorganic geopolymer, and in which the particles are distributed in the macropores and / or in the sides or walls.

[0003] The matrix can also be called the "skeleton".

[0004] The particles may in particular be active particles, in particular inorganic solid metal cation exchanger compound particles, adsorbent particles or catalyst particles.

[0005] The material according to the invention may in particular be in the form of a monolith.

[0006] The invention also relates to a method for preparing said material.

[0007] The invention can be applied in various fields, such as catalysis, metal cation separation or solid phase extraction in combination with selective adsorbents such as zeolite particles.

[0008] The invention can be more particularly applied in the field of effluent treatment, in particular liquid effluent treatment, in particular radioactive liquid effluent treatment, in particular to remove metal cations, such as strontium cations, therefrom.

[0009] Therefore, the present invention also relates to a method for separating metal cations, in particular radioactive or toxic metal cations, contained in a medium, in particular a liquid medium, using the material. Background Art

[0010] Materials suitable for fixed bed processes should have multiple porosities to optimize the transport of the ions or molecules of interest and should be of sufficient size to act as a bed while limiting material losses as much as possible. These materials with multiple porosities are particularly macroporous materials that contain active sites consisting of active particles of nano-, submicron- or micron-size in their pores.

[0011] According to the first method, nano-, submicron or micron active particles obtained elsewhere and an inorganic binder are granulated to prepare these porous materials containing nano-, submicron or micron active particles in their pores.

[0012] The resulting granules are then cold pressed, during which the binder provides the powder mixture with cohesion. In direct compression, the binder can be in dry form; in wet granulation, the binder can be applied via an aqueous medium. In wet granulation, the nano-, submicron- or micron-active particles are suspended in a binder (which will ensure cohesion) and subsequently extruded or subjected to a thermal treatment such as drying or sintering. The most commonly used inorganic binders are clay-based binders. This method is industrially suitable and simple, and is also suitable for any type of granules. However, the porosity of the material obtained by this method is not controlled, so for fixed-bed applications, the transport properties (fluid mechanics and diffusion properties) of the material are poor. In addition, the mechanical strength of the "pressed tablets" obtained is low [1].

[0013] According to a second method, these porous materials containing nano-, submicron- or micron-active particles in their pores are prepared by conversion of porous materials obtained elsewhere (eg porous silica such as silica gel, porous glass, sol-gel silica).

[0014] The second approach involves chemically treating a substrate with well-controlled porosity to obtain the desired properties of nano-, sub-micron- or micron-particles [2-3].

[0015] This method is not suitable for all types of active particles, as different types of particles have different compositions and therefore require specific treatment methods. The method is complex and requires several steps, making it difficult to convert industrially. In addition, the method can lead to pore blockage, which in turn renders the active sites ineffective.

[0016] According to the third method, these porous materials containing nano-, submicron- or micron-active particles in their pores are prepared by functionalizing the porous material. This method involves pre-functionalizing the porous material that acts as a "skeleton" and then gradually growing the active material in the pre-functionalized grafted skeleton structure [4-5].

[0017] Likewise, the method is complex and requires several steps, is difficult to transfer to other types of particles, and can also result in pore blockage.

[0018] According to a fourth method, a porous material substrate is impregnated with a suspension containing these nano-, submicron or micron active particles to prepare these porous materials containing nano-, submicron or micron active particles in their pores [6-7].

[0019] The method is simple to implement but requires several impregnation steps. These impregnation steps are difficult to control and, on the one hand, they lead to pore blockage in the porous material matrix and, on the other hand, they do not allow for perfect control of the number of particles inserted into the matrix or the uniformity of the particles' insertion into the pore network. In addition, sometimes the particles have poor adhesion to the matrix, which can lead to loss of active particles when the material is applied to fixed-bed effluent treatment. In addition, the mechanical strength of the material prepared by this method is low [6].

[0020] According to the fifth method, these porous materials containing nano-, sub-micron or micron active materials in their pores are prepared using an oil-in-water emulsion containing nano- or sub-micron active particles. This method stabilizes the emulsion by surfactants, or by active particles (Pickering type emulsion), or by a combination of both. When the oil phase is extracted, the inorganic oxide precursor in the aqueous phase can increase the adhesion of the mixture by forming a skeleton [8-9]. This method requires that the skeleton is composed of oxides (mainly using silicon dioxide), which involves sol-gel synthesis, which is complex to control, the precursors (alcohol salts) are expensive and difficult to industrialize.

[0021] Furthermore, this method is limited to the insertion of active particles of small size (a few hundred nanometers at most), making it difficult to adapt to other types of active particles and difficult to manage industrially.

[0022] Finally, the cellular porous structure of the obtained materials does not endow them with good hydrodynamic transport properties for fixed-bed applications, which may make it difficult for the effluent to be treated to access a portion of the active particles incorporated in the material's skeleton.

[0023] Therefore, in view of the above, there is still an unmet need for materials with multiple porosity, in particular materials with interconnected macropores: such materials should have high mechanical strength and can incorporate active particles, these active particles should be incorporated uniformly and their incorporation should be in a way that these active particles are easily accessible to the emissions circulating in the macropores, in any case more easily accessible than in the materials of the prior art.

[0024] It should also have a variety of shapes and sizes (for example, from millimeters to tens of centimeters).

[0025] A first object of the present invention is to provide a material which meets the above requirements.

[0026] A further object of the present invention is to provide a material which overcomes the drawbacks, limitations and disadvantages described in the prior art, in particular in the prior art documents cited above.

[0027] Furthermore, there is a need for a method for preparing such a material which is reliable, has a limited number of steps, is versatile and can be applied to all types of active particles, regardless of their nature and size (e.g. nano, micro or submicron). In particular, the method must be simple to implement, reproducible and easily industrializable.

[0028] The second object of the present invention is to provide a preparation method that meets the above requirements. Summary of the invention

[0029] The above first and other objects of the present invention are to provide a solid material with open, multiple and at least partially interconnected pores, which comprises an (inorganic) matrix made of a microporous-mesoporous geopolymer and particles of at least one solid compound that is different from, phase-separated and distinct from the geopolymer, wherein the matrix has at least partially interconnected open macropores surrounded by sides (surfaces, faces) or walls formed by the microporous-mesoporous geopolymer, and the particles are distributed in these macropores and / or these sides or walls.

[0030] The term "geopolymer" or "geopolymer matrix or skeleton" means, within the scope of the present invention, a solid porous material in the dry state obtained by hardening a mixture containing a finely ground material (i.e., usually an aluminosilicate source) and a salt solution (i.e., an activation solution), which mixture is able to solidify and harden over time. The mixture may also be referred to by the terms "geopolymer mixture", "geopolymer composition" or "geopolymer paste". The hardening of the geopolymer is obtained by dissolving / polycondensing the finely ground geopolymer mixture in a salt solution, such as a high pH salt solution (i.e., an activation solution).

[0031] More specifically, the geopolymer or geopolymer matrix or skeleton is an amorphous aluminosilicate inorganic polymer. The polymer is obtained by reacting a reactive material (i.e., an aluminosilicate source) containing essentially silicon dioxide and aluminum, which is activated by a strongly alkaline solution (activating solution) and is formulated with a low solid / solution mass ratio. The structure of the geopolymer is composed of a Si-O-Al lattice formed by tetrahedra of silicate (SiO4) and aluminate (AlO4) bonded at their vertices by shared oxygen atoms. The lattice has one or more charge compensating cations (also called compensating cations) that can compensate for the AlO4 - The compensating cation is advantageously selected from the group consisting of alkali metals such as lithium (Li), sodium (Na), potassium (K), rubidium (Rb) and cesium (Cs), alkaline earth metals such as magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba) and mixtures thereof.

[0032] According to the present invention, the geopolymers as defined above are macroporous, mesoporous and microporous, generally having a density of less than 1.5 g / cm 3 , especially less than 1.2g / cm 3 , especially less than 0.9g / cm 3 , more specifically less than 0.6 g / cm 3 density.

[0033] The term "macroporous geopolymer" refers to a geopolymer having macropores; the term "mesoporous geopolymer" refers to a geopolymer having mesopores; the term "microporous geopolymer" refers to a geopolymer having micropores.

[0034] According to the present invention, the term "macropores" means pores having an average size (usually defined by the diameter of their cross section, since pores generally have a circular cross section) greater than The term "mesopores" refers to pores with an average size of 20 to The term "micropores" means pores with an average size smaller than (e.g. 5 to ) hole. Note that

[0035] The mesoporosity is typically between 20 and 33 volume % relative to the total porosity of the geopolymer.

[0036] The geopolymer forming the matrix, the skeleton, of the material according to the invention also comprises macropores defined in said skeleton, said matrix.

[0037] The macroporosity is typically between 20 and 80 volume % relative to the total porosity of the geopolymer.

[0038] Porosity can be measured by nitrogen adsorption-desorption or mercury intrusion porosimetry.

[0039] The microporosity is typically less than 15% by volume, in particular less than 10% by volume, in particular 5% to 10% by volume, relative to the total porosity of the geopolymer.

[0040] In the geopolymer, the total porosity corresponding to the macroporosity, mesoporosity and microporosity is greater than 70% by volume, in particular greater than 75% by volume, in particular greater than 80% by volume, relative to the total volume of the geopolymer.

[0041] The material according to the invention is a solid material having open multiple porosity (ie having macropores, micropores and mesopores) and at least partially or even completely interconnected pores, also called material having open hierarchical and at least partially or completely interconnected pores.

[0042] More precisely, the material according to the invention has open and connected (or interconnected) pores.

[0043] According to the invention, the porosity is multivariate, ie it comprises macropores, micropores and mesopores simultaneously.

[0044] The pores are also open, i.e., accessible to fluids (such as emissions) in contact with the material. The pores are also at least partially connected (or interconnected), or fully interconnected, i.e., fluids can pass through the material through the interconnected pores. The pores also ensure that the particles are accessible to the fluid.

[0045] The concept of open porosity applies to all pores of a material, i.e., to mesopores, micropores and mesopores. The pores (macroporous, micropores and mesopores) are open and all at least partially connected, interconnected, or even completely connected, interconnected (regardless of their size) to each other.

[0046] Thus, the macropores may be connected to each other and to the mesopores and / or micropores, the mesopores may be connected to each other and to the micropores and / or macropores, and the micropores may be connected to each other and to the macropores and / or mesopores.

[0047] Not only does the presence of micropores and mesopores lead to the opening and interconnection of macropores, but two macropores can also be interconnected with each other.

[0048] In summary, macropore interconnection is independent of the presence of mesopores and micropores.

[0049] Surprisingly it was observed that due to the presence of particles, in particular active particles, in the material according to the invention the macropore interconnectivity is greatly increased compared to the same material without particles and furthermore does not have partially closed cellular macropores (see Examples).

[0050] Advantageously, the geopolymer used within the scope of the present invention has permeable macropores connecting a first major surface to a second major surface of the geopolymer material.

[0051] According to the invention, the term "major surface" denotes the outer part of a material, which is the outer part of the material relative to its environment. A major surface typically has cavities, in particular macroscopic, interconnected cavities.

[0052] The material according to the invention has a specific structure which has never been described or suggested in the prior art and furthermore consists of specific materials, namely in particular geopolymers which constitute the skeleton, the matrix, of the material according to the invention.

[0053] The material according to the invention further comprises particles of at least one solid compound other than a geopolymer accessible in the matrix, such as active particles.

[0054] According to the invention, apart from the particles of at least one solid compound different from the geopolymer (such as active particles), it is important to choose the nature and size of the particles of at least one solid compound different from the geopolymer almost without restriction and independently of the geopolymer matrix.

[0055] In fact, the material according to the invention can first be defined as a material with multiple or hierarchical porosity, or as a material with different pore scales, more specifically three pore scales, which has a matrix or skeleton in which at least partially interconnected open macropores (in other words, open and at least partially interconnected macropores) surrounded by microporous-mesoporous sides (surfaces, faces) or walls are defined. Therefore, the material according to the invention comprises a combination of macropores, mesopores and micropores. Moreover, in the material according to the invention, the macropores are open and at least partially interconnected, or even completely interconnected, and do not have a completely cellular structure, which is unexpectedly due to the presence of particles of at least one solid compound different from the geopolymer in the material according to the invention.

[0056] In the material according to the invention, open, interconnected macropores enable the transport of fluids, such as emissions, within the material, and open and interconnected mesopores and micropores ensure that particles of at least one solid compound other than geopolymer are easily accessible if these particles are located within the walls and sides of the macropores.

[0057] In other words, the interconnection between multiple porosities and macropores can optimize the transport of fluids such as emissions within the material, allowing them to reach particles smoothly.

[0058] It should be noted that good interconnection allows the particles of at least one solid compound other than geopolymer to be in good contact with the fluid, but there are other possible scenarios. It is possible to obtain substantially interconnected macropores, but the particles are completely embedded and aggregated in the walls and sides. If the walls and sides are neither mesoporous nor microporous, then these particles cannot be in contact with the fluid and the material will not achieve satisfactory results. In the material according to the invention, the particles are in good contact with the fluid due to the open and interconnected micropores and mesopores, especially with macropores.

[0059] The mechanical strength of the material according to the invention is ensured by the very strong geopolymer skeleton, usually aluminosilicate.

[0060] In general, geopolymer matrices have many advantages over metal oxide matrices.

[0061] The synthesis of geopolymers is more easily controlled than the synthesis of metal oxides by the sol-gel method.

[0062] Compared to the precursors used to synthesize metal oxides (mainly alkoxides), the synthetic precursors of geopolymers are cheaper.

[0063] The geopolymer matrix has superior mechanical strength than the metal oxide matrix.

[0064] The geopolymer matrix has mesopores, whereas the metal oxide matrix does not have any mesopores. To create mesopores in the metal oxide, additional compounds need to be added to the emulsion formulation, thereby making the system more complex.

[0065] Finally, in summary, the material according to the present invention has a hierarchical porosity, is mechanically strong and incorporates particles, usually active particles (for example for specific applications in the case of treating fluids such as liquid or gaseous emissions), and due to the interconnections between the macropores, the fluid to be treated, such as the emission, can have increased contact with the particles distributed in the material.

[0066] In other words, the material according to the invention has open and interconnected macropores, intercalated with particles of at least one solid compound different from a geopolymer, which particles can come into contact with a fluid.

[0067] Advantageously, the material according to the invention may be in the form of particles (in which case these particles are not particles of at least one solid compound different, distinct, phase-separated from the geopolymer), such as grains, pellets or beads; or in the form of a monolith.

[0068] A particle or monolith of material may have a size (typically defined by its largest dimension, such as its diameter) ranging from 300 micrometers (μm) to tens or tens of centimeters (cm), such as 10, 10, 30, 40, 50, or even 100 cm.

[0069] Thus, the term "size" generally refers to the largest dimension of a particle or monolith of material.

[0070] The 300 to 500 micron size is particularly suitable for use in a fixed bed via a packed column.

[0071] According to the invention, the term "monolith" means a solid body whose average size is at least 1 mm.

[0072] Advantageously, the particles of the at least one solid compound different from the geopolymer may have an average size, such as a diameter, of 2 nm to 100 μm, preferably 10 nm to 10 μm.

[0073] The term "size" herein also refers to the largest dimension, such as a diameter, of particles of the at least one solid compound other than the geopolymer.

[0074] The size of the particles of the at least one solid compound different from the geopolymer can be selected for a specific targeted application.

[0075] Advantageously, the particles of at least one solid compound different from the geopolymer may be chosen from the group consisting of: nanoparticles, submicron particles and micron particles.

[0076] According to the present invention, the term "nanoparticles" refers to particles whose average size (usually defined by their diameter) is 2 to 100 nm; the term "submicron particles" refers to particles whose average size (usually defined by their diameter) is 100 nm to 1 μm; the term "micron particles" refers to particles whose average size (usually defined by their diameter) is 1 to 100 μm.

[0077] The particles of at least one solid compound other than the geopolymer may be completely inorganic mineral particles, ie particles consisting exclusively (100%) of one or more inorganic solid compounds.

[0078] The particles of at least one solid compound different from a geopolymer may be partly organic particles, ie particles comprising one or more inorganic solid particles and one or more organic solid compounds, such as in particular “MOF” particles (see below).

[0079] Advantageously, the particles of at least one solid compound different from the geopolymer may be particles of an active compound, or only active particles.

[0080] The terms "active particles" or "particles of active compounds" generally denote (in contrast to inert particles) particles which are capable of playing a role in chemical, physical or physicochemical processes (such as chemical reactions, adsorption phenomena, catalytic processes, etc.), for example in catalysis or extraction, in particular for the treatment of liquid or gaseous effluents.

[0081] Preferably, the active particles are selected from the group consisting of particles of at least one solid metal cation exchanger compound, catalyst particles and adsorbent compound particles.

[0082] Advantageously, the solid metal cation exchanger compound may be selected from the group consisting of: zeolites; alkaline titanosilicates; coordination polymer (metal-organic framework) particles and mixtures thereof.

[0083] There are no restrictions as to the particle shape of the at least one solid compound other than the geopolymer.

[0084] Advantageously, the particles of at least one solid compound different from the geopolymer may have the shape of a sphere or ellipsoid, or a needle-like shape.

[0085] Advantageously, the content of particles of at least one solid compound different from the geopolymer is between 0.1 and 30% by mass, preferably between 5 and 15% by mass, relative to the total mass of the material.

[0086] A second object of the present invention is to provide a process for preparing the material according to the present invention as described above.

[0087] The preparation method comprises at least the following steps:

[0088] a) preparing an oil-in-water emulsion formed by droplets of the oil phase dispersed in a continuous aqueous phase and particles of at least one solid compound (different, distinct, phase-separated from the geopolymer) by treating a mixture comprising an oil phase and an aqueous phase by mechanical agitation with shear, the aqueous phase comprising an activation solution, an aluminosilicate source, and optionally a surfactant. The aluminosilicate source is capable of forming a geopolymer by dissolution / polycondensation in the activation solution. These particles are present at the interface formed by the continuous aqueous phase of the emulsion and the oil phase droplets, wherein the oil phase droplets are dispersed in the continuous aqueous phase;

[0089] b) allowing the emulsion to stand and be shaped to obtain a selected size and shape and to form a geopolymer matrix by polycondensation;

[0090] c) removing the oil phase to obtain the material according to the invention as described above.

[0091] Advantageously, the emulsion is formed in a mould of selected size and shape.

[0092] The method according to the invention comprises a specific sequence of specific steps which has never been described or suggested in the prior art, as represented in particular by the documents cited above.

[0093] The method according to the invention enables the synthesis and preparation of the material according to the invention, i.e. a material with hierarchical porosity, which has a strong structure and incorporates particles, in particular active particles (for example active particles with specific applications in the case of treating liquid or gaseous emissions), which can increase the contact of the particles with the fluid to be treated (such as the emission).

[0094] The method according to the invention enables the synthesis of such materials with controlled shapes and sizes, for example from one millimeter to several tens of centimeters (see above), without the need for grinding or compacting after synthesis.

[0095] Importantly, the method according to the invention enables the synthesis of such materials without any restrictions on their size and shape.

[0096] Thus, for example, the size of the mould that can be used only during step b) will limit the size of the final material shaped (in other words, the object consisting of this material).

[0097] The method according to the invention is characterized in particular by the use of the reagents required for the synthesis of an inorganic binder based on a geopolymer within the continuous phase of an emulsion comprising particles of at least one solid compound different from the geopolymer, such as active particles.

[0098] According to the invention, the process for preparing the emulsion is optimized, in particular to provide a better interconnection between the macropores in the geopolymer framework, so that the fluid circulating in the material can better contact the active particles.

[0099] According to the invention, in a novel and unexpected way, particles of at least one solid compound different from the geopolymer (such as active particles) and optionally a surfactant and a scheme comprising at least one sequence (for example 2 homogenization sequences) are used to stabilize an emulsion having an activated aqueous solution of a geopolymer as a continuous phase.

[0100] The latter two parameters (ie, stabilization using particles and optionally surfactants and a scheme comprising at least one homogenization sequence) enable the formation of pores, especially macropores, which are non-cellular and better interconnected, allowing better fluid contact with the active particles.

[0101] In other words, in the method according to the invention, during step a), an oil-in-water emulsion is prepared, more specifically an oil phase dispersed in a continuous aqueous phase comprising an activation solution and a source of aluminosilicates capable of forming a geopolymer by dissolution / polycondensation. This emulsion is stabilized in the presence of particles of at least one solid compound different from the geopolymer, in particular active particles. Sometimes it is necessary to add a surfactant that has a synergistic effect with the particles in order to stabilize the emulsion.

[0102] The parameters of the emulsion, in particular the size of the oil phase droplets, are controlled by controlling the different steps (including steps a3) and a4) described below) to control the final porosity of the material.

[0103] An aluminosilicate source is inserted to obtain a geopolymeric inorganic binder in the aqueous phase of the emulsion by a dissolution-polycondensation process.

[0104] The emulsion prepared in step a) generally comprises from 40% to 80% by volume, preferably from 50% to 60% by volume, of oil phase relative to the total volume of the emulsion.

[0105] The solid particle concentration in the emulsion may be 0.05% by mass to 20% by mass, preferably 1% by mass to 10% by mass.

[0106] The oil phase of the mixture usually consists of one or more oils.The term "oil" is well known and widely used by those skilled in the art.

[0107] Any type of oil may be used in accordance with the method of the invention.

[0108] Advantageously, the oil phase of the mixture is generally constituted by one or more linear or branched alkanes having from 7 to 22 carbon atoms, preferably from 12 to 16 carbon atoms, such as dodecane and hexadecane.

[0109] Preferably, the oil phase of the mixture consists of dodecane.

[0110] The mechanical stirring carried out in step a) is mechanical stirring with shearing.

[0111] Advantageously, the shear rate ranges from 1000 to 20000 rpm, preferably from 2000 to 15000 rpm, more preferably the shear rate is 10000 rpm.

[0112] The size of the macropores of the material can be controlled by the shear rate acting on the emulsion. When the shear rate increases, the size of the macropores decreases.

[0113] The mechanical agitation with shearing (mechanical agitation and shearing) performed during step a) can be performed by different methods, each of which can achieve a specific porosity. In fact, a higher shear rate will form smaller macropores than a lower shear rate. Thus, the shearing of the emulsion can be performed by mechanical shearing using a homogenizer, or ultrasonic shearing using ultrasound.

[0114] Preferably, the mechanical agitation with shearing carried out during step a) is carried out by a device intended for emulsification such as Step a) can be described as a step of emulsifying the above mixture.

[0115] In other words, the term mechanical stirring with shear generally refers to mechanical stirring using a stirring device equipped with an impeller shaft or, preferably, a homogenizing or dispersing device (e.g. Ultra-Turrax, type) (can be equipped with a dispersion rod with a rotor / stator system).

[0116] As already indicated above, advantageously, the shear rate set by the homogenizing or dispersing device is in the range of 1000 to 20000 rpm, preferably 2000 to 15000 rpm, more preferably a shear rate of 10000 rpm.

[0117] In the present invention, the expression "aluminosilicate source" and the expression "reagent material containing essentially silicon dioxide and aluminum" are similar and can be used interchangeably.

[0118] The reagent material containing essentially silicon dioxide and aluminum that can be used to prepare the geopolymer matrix of the material according to the invention is advantageously a solid source containing amorphous aluminosilicates. These aluminosilicates are especially chosen from natural aluminosilicate minerals such as illite, stilbite, kaolinite, pyrophyllite, andalusite, bentonite, kyanite, milanite, grovenite, chlorite, cordierite, feldspar, allophane, etc.; calcined natural aluminosilicate minerals such as metakaolin; synthetic glasses based on pure aluminosilicates; high-alumina cement; pumice; calcination by-products or residues from industrial processes such as fly ash or blast furnace slag, obtained respectively from coal combustion and from the conversion of iron ore into cast iron in a blast furnace; and mixtures thereof.

[0119] The term "activation solution" denotes a high pH saline solution well known in the field of geopolymerization. The latter is a strongly alkaline aqueous solution which may optionally contain a silicate compound, in particular selected from the group consisting of silicon dioxide, colloidal silicon dioxide and vitreous silicon dioxide.

[0120] The expressions "activation solution", "high pH salt solution" and "strong alkaline solution" are similar in the present invention and can be used interchangeably.

[0121] The term "strong alkaline" or "high pH" refers to a solution in which the pH is greater than 9, especially greater than 10, in particular greater than 11, more particularly greater than 12. In other words, the activated solution has an OH - The concentration is greater than 0.01M, especially greater than 0.1M, particularly greater than 1M, more particularly 5 to 20M.

[0122] The activation solution comprises a compensating cation or a compensating cation mixture as defined above in the form of an ionic solution or salt. Thus, the activation solution is particularly selected from aqueous solutions of sodium silicate (Na2SiO3), potassium silicate (K2SiO2), sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), cesium hydroxide (CsOH) and derivatives thereof.

[0123] During step b), the emulsion is left to stand in order to form the geopolymer skeleton by polycondensation in the continuous phase of the emulsion.

[0124] During the resting step, the size and shape of the final material can be defined due to the processability of the synthetic emulsion. Thus, monoliths, beads or grains can be obtained, depending on the processability of the emulsion.

[0125] The term "processability" refers to the ability of an emulsion to be shaped (eg, using a mold) for a certain time interval before hardening to form the final material (ie, when the emulsion has a still liquid or gelled appearance, before hardening and shaping the material).

[0126] This step can be performed by leaving the emulsion obtained in step b) at a temperature of 10° C. to 60° C., for example at a temperature of 40° C. for a sufficient time to form the material according to the present invention. The time can be, for example, 2 hours to 3 weeks, for example 24 hours to 7 days.

[0127] During step c), the oil phase present in the pores of the material is removed.

[0128] The oil phase may be removed by any technique known to those skilled in the art.

[0129] The oily phase can especially be removed by washing, for example in a Soxhlet extractor, followed by drying, treatment with a supercritical fluid such as supercritical CO 2 , hydrothermal treatment, thermal treatment, or a combination of these different treatment methods.

[0130] Washing can remove organic residues from the oil phase, which are primarily present in the macropores.

[0131] The washing may be performed with an organic solvent such as THF, acetone and mixtures thereof (eg, a THF-acetone mixture, preferably a 50:50 mixture of THF and acetone).

[0132] The wash may last from 12 to 36 hours, for example 24 hours.

[0133] Preferably, the washing is performed by refluxing the organic solvent.

[0134] Drying may be carried out by evaporating the organic solvent used for washing at ambient temperature, typically over a period of 5 to 10 days (eg 7 days).

[0135] Alternatively, drying may be performed with heating to a temperature of, for example, 90°C.

[0136] Drying can also be carried out using supercritical fluids such as supercritical CO2.

[0137] Using the method according to the invention, a material according to the invention is obtained, i.e. a macroporous material (in which the macropores are generated by the oil phase), comprising particles, preferably active particles, especially nano-, submicron or micron particles (especially for stabilizing emulsions (but also for the application sought for the material), optionally with the synergistic assistance of surfactants). The porosity, the mechanical strength (provided by the geopolymer backbone of the material), the shape and size of the material, the nature and size of the active sites are thus controlled simultaneously.

[0138] The method is simple to implement and can be easily converted to industry.

[0139] In summary, the advantages and unexpected effects of the method according to the invention for manufacturing, preparing the material according to the invention, i.e. the material with multiple porosity comprising active particles, are listed in particular below. Some advantages of the method are related to the material obtainable by the method and have been essentially described above:

[0140] Fully control the interconnectivity between multiple porosities and macropores by controlling the emulsion (especially the size of the oil phase droplets), thereby optimizing the transport of fluids (such as emissions) within the material and the contact between the fluids and the active particles.

[0141] The meso- and micro-pores of the geopolymer matrix ensure increased contact of the active particles with the fluid on the walls and sides of the macropores of the incorporated material.

[0142] The mechanical strength of the final material is ensured by a strong aluminosilicate geopolymer skeleton.

[0143] It is very important that the method according to the invention can be used with any type of particles, in particular with active particles, without being limited by their nature, size (in particular 2 nm to 100 μm, preferably 10 nm to 10 μm), and their particle size distribution, which can be nanometer-sized, submicrometer-sized or even micrometer-sized.

[0144] To this end, only the parameters need to be adjusted to obtain and stabilize the starting emulsion.

[0145] • The size of the active sites corresponds directly to the size of the particles (nanometer, submicrometer or micrometer) incorporated into the formulation of the material according to the invention and obtained elsewhere.

[0146] • The dimensions of the final shaped material obtained are completely modular and depend, for example, on the mould in which step b) is carried out.

[0147] • The process according to the invention is carried out under mild conditions, at low temperatures, generally at ambient temperature and atmospheric pressure.

[0148] The process according to the invention uses inexpensive and non-toxic reagents, in particular the activation solution and the aluminosilicate source.The reaction medium is essentially aqueous.

[0149] The method according to the invention is simple, reliable and easy to implement, and the method uses reagents that are easily available at low cost. The method can be carried out with simple equipment and devices. In particular, according to the method of the invention, all steps (including steps a3) and a4) described below) can be carried out in a single reactor. In other words, the method according to the invention can be described as a "one-pot" method.

[0150] Thus, step b) may be carried out in a single reactor or container (the same reactor used in step a)), the container or reactor used to produce the emulsion during step a) subsequently being used as a mold during steps b) and c).

[0151] • The process according to the invention can be easily scaled up to industrial scale.

[0152] Advantageously, before step a), the following sub-steps a1) to a4) are carried out to prepare a mixture comprising an oil phase and an aqueous phase:

[0153] a1) preparing an aqueous suspension of particles of at least one solid compound (different from, distinct from, phase-separated from the geopolymer), preferably an aqueous suspension of active particles, in water or in an aqueous solution comprising a surfactant;

[0154] a2) adding an oily phase to the aqueous suspension of particles obtained at the end of step a1), thereby obtaining a biphasic mixture comprising the oily phase and an aqueous phase consisting of the aqueous suspension;

[0155] a3) adding an activated aqueous solution (alkaline silicate) to the aqueous phase of the biphasic mixture obtained at the end of step a2);

[0156] a4) adding a source of aluminosilicates capable of forming a geopolymer by dissolution / polycondensation to the aqueous phase of the biphasic mixture obtained at the end of step a3).

[0157] Typically, the aqueous suspension of particles prepared in step a1) has a particle concentration of 2 g / L to 1000 g / L.

[0158] The concentration of particles in the suspension is chosen as a function of the final concentration of particles of at least one solid compound different from the geopolymer sought in the prepared material.

[0159] The surfactant may be selected from anionic, cationic, nonionic surfactants and mixtures thereof. An example of a surfactant is tetradecyltrimethylammonium bromide (TTAB).

[0160] The concentration of the surfactant in the aqueous suspension prepared in step a1) is generally between 0.1% and 20% by mass relative to the mass of the particles.

[0161] Advantageously, after step a2) and before step a3), the biphasic mixture comprising the oil phase and the aqueous phase consisting of the aqueous suspension is subjected to mechanical stirring with shear; and / or after step a3) and before step a4), the biphasic mixture is subjected to mechanical stirring with shear.

[0162] This mechanical agitation with shear has been described in detail above.

[0163] The invention also relates to the use of the material according to the invention for catalyzing a chemical reaction, for filtering a fluid, or for separating or extracting substances contained in a fluid. The fluid may be in any physical state, in particular in the liquid or gaseous state.

[0164] The material according to the invention can be used in particular, but not exclusively, for separating at least one metal cation or metalloid cation from a liquid medium, wherein the liquid medium is contacted with the material according to the invention.

[0165] The medium can be a liquid or a gaseous medium.

[0166] The material according to the invention is particularly suitable for such applications due to its excellent properties, such as excellent exchange capacity, excellent selectivity and high reaction rate.

[0167] This superior efficacy is achieved by reducing the amount of active particles (eg, inorganic solid metal cation exchanger compounds such as zeolite particles).

[0168] Furthermore, the excellent mechanical strength and mechanical stability of the material according to the invention, resulting from its specific structure, can be adjusted in columns and in continuous separations and can therefore be easily integrated into existing equipment, for example into processing chains or threads comprising several steps.

[0169] Advantageously, the liquid medium may be an aqueous liquid medium, such as an aqueous solution.

[0170] The liquid medium may be a process liquid or an industrial effluent.

[0171] Advantageously, the liquid medium may be chosen from liquids and effluents obtained from the nuclear industry and from installations and processes using radionuclides.

[0172] Generally, the cation concentration may be from 0.1 picogram to 500 mg / L, preferably from 0.1 picogram to 100 mg / L.

[0173] The term "metal" also covers isotopes of said metal, especially radioactive isotopes, and the term "metalloid" also covers isotopes of said metal, especially radioactive isotopes.

[0174] Advantageously, the cation may be a cation chosen from the alkali metals, alkaline earth metals, transition metals, heavy metals, rare earth elements (scandium, yttrium and lanthanides), actinides, noble gases, and isotopes thereof, in particular radioactive isotopes.

[0175] Zeolites are particularly suitable for separating such cations.

[0176] For example, the cation may be a cation selected from Sr, Cs, Co, Ag, Ru, Fe and Tl and isotopes thereof, in particular radioactive isotopes.

[0177] In particular, the cation may be 134 Cs, or 137 Cs, or 90 Sr cation.

[0178] The method has all the advantages inherently associated with the materials according to the invention, used in the method and which have been described above.

[0179] The invention will now be described in more detail hereinafter, in particular in conjunction with specific embodiments of the invention serving as the subject of examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0180] Figure 1 is an image of the zeolite LTA submicron particles prepared in Example 1 taken using a scanning electron microscope (SEM).

[0181] Figure 1 The scale bar used in the figure represents 1 μm.

[0182] Figure 2 is a photograph of a monolith prepared in Example 1 using Protocol P0, the monolith comprising a geopolymer incorporating submicron particles of zeolite LTA.

[0183] Figure 3A and

[0184] Figure 3B SEM images of the interior of the monoliths prepared in Example 1 and Example 1A are shown, respectively.

[0185] Figure 3A and 3B The scale bar used in the figure represents 70 μm.

[0186] Figure 4 is a graph showing the pore size distribution in a purely synthesized geopolymer (Example 1B) (curve A) and in two geopolymers synthesized using the P0 protocol containing zeolite (Example 1) (curve B) and synthesized using the P0 protocol without zeolite (Example 1A) (curve C).

[0187] The x-axis represents the pore diameter (in nm) and the y-axis represents the pore volume (in cm) 3 / g.nm).

[0188] Figure 5are diffraction patterns showing submicron zeolite LTA (curve A), a geopolymer synthesized using the P0 protocol without zeolite (Example 1A) (curve B), and a geopolymer synthesized using the P0 protocol with zeolite LTA (Example 1) (curve C).

[0189] The x-axis represents 2θ (in degrees) and the y-axis represents intensity (in arbitrary units).

[0190] Fig. 6A

[0191] Figure 6B and

[0192] Figure 6C According to the scheme P1 ( Fig. 6A )、Scheme P2( Figure 6B ) and Plan P3( Figure 6C ) SEM image of the geopolymer monolith prepared in Example 2.

[0193] Fig. 6A , 6B The scale bar used in and 6C represents 70 μm.

[0194] Figure 7 is a graph showing the pore size distribution in monoliths prepared in Example 2 using Protocols P1, P2 and P3.

[0195] The x-axis represents the pore diameter (in nm) and the y-axis represents the pore volume (in cm) 3 / g.nm).

[0196] Figure 8 is a bar graph showing Kd values ​​(in mL / g) determined for a geopolymer prepared according to protocol PO (not comprising submicron zeolite particles) and geopolymer monoliths prepared according to protocols PO, PI, P2 and P3 (comprising zeolite particles) (Example 3).

[0197] Fig. 9 is a SEM image of the micron zeolite particles used in Example 4.

[0198] Fig. 9 The scale bar used in the figure represents 5 μm.

[0199] Fig.10 is a diffraction diagram showing micron particles of zeolite 4A (curve A), a geopolymer prepared according to protocol P3 without comprising particles of zeolite 4A (curve B) and a geopolymer prepared according to protocol P3 comprising particles of zeolite 4A (curve C) (Example 4B).

[0200] The x-axis represents 2θ (in degrees) and the y-axis represents intensity (in arbitrary units).

[0201] Fig.11 is a graph showing the particle size distribution of the CST nanoparticles used in Example 5.

[0202] The x-axis represents size (in μm) and the y-axis represents % (in number).

[0203] Fig.12 is a diffraction pattern showing CST nanoparticles (curve A), a geopolymer prepared according to protocol P3 without comprising CST (curve B) and a geopolymer prepared according to protocol P3 comprising CST nanoparticles (curve C) (Example 5B).

[0204] Fig.13 is a graph showing the nitrogen adsorption isotherm on pure geopolymer. The x-axis represents the relative pressure (P / P°) and the y-axis represents the amount of nitrogen adsorbed (in cm 3 / g). DETAILED DESCRIPTION

[0205] The invention will now be described with reference to the following examples, which are given by way of illustration and not limitation.

[0206] Examples .

[0207] Example 1 :

[0208] In this example, the manufacture of a monolithic material comprising a geopolymer incorporating submicron zeolites according to the present invention was performed.

[0209] More precisely, in this example, according to the invention, submicron particles of zeolite LTA, known to be an efficient and selective adsorbent of Sr in aqueous media, are incorporated into the "skeleton" of a macroporous geopolymer matrix.

[0210] Synthesis of submicron particles of zeolite LTA.

[0211] The scheme for synthesizing zeolite LTA submicron particles is as follows:

[0212] - 2.65 g of NaOH pellets (purchased from Sigma-Aldrich ) and 5.75 g of NaAlO2 powder (purchased from ) were dissolved in 26.25 mL and 35 mL of water, respectively.

[0213] -The two solutions were then mixed in the autoclave with vigorous stirring for several minutes.

[0214] - Then 2g of SiO2 powder ( 380, purchased from Evonik Industries ),) are added into the autoclave, and the autoclave is sealed airtight.

[0215] - Heat treatment: 40°C for 20 h, then 70°C for 24 h.

[0216] - The powder obtained was recovered by filtration, washed with water and dried at 80°C overnight.

[0217] Finally, submicron particles of zeolite LTA with a size of 300 to 500 nm were obtained (see Figure 1 ).

[0218] - Preparation of a monolith comprising a geopolymer incorporating submicron particles of zeolite LTA.

[0219] The protocol for synthesizing a geopolymer comprising submicron particles incorporating zeolite LTA synthesized as described above is protocol P0, which first comprises the following steps:

[0220] - Step 1: 617 mg of zeolite LTA powder (consisting of submicron particles) was added to 1.774 mL of an aqueous solution concentrated to 34.8 g / L using a surfactant, i.e., tetradecyltrimethylammonium bromide (TTAB) (purchased from Sigma-Aldrich). -1 The concentrated aqueous solution to which the powder was added was placed in an ultrasonic bath for 15 minutes.

[0221] - Step 2: To the concentrated aqueous solution to which the powder was added, 5 mL of an oil phase, ie, dodecane (purchased from Sigma-Aldrich) was added.

[0222] - Step 3: Add 2.12 mL of a solution consisting of 81% by mass of K5020T (purchased from ) (based on a modified potassium silicate aqueous solution consisting of 30 mass % SiO2, 18 mass % K2O and 52 mass % H2O) and 19 mass % KOH (85%, purchased from Sigma-Aldrich).

[0223] - Step 4: Add 2.64 g of metakaolin powder ( Purchased from BASF).

[0224] - "UT" Step 5: Finally, use the Ultra- The mixture was sheared by a homogenizer at a shear rate of 10,000 rpm for 1 minute.

[0225] At the end of step 5, an emulsion is thus obtained.

[0226] The viscous emulsion was placed in a cylindrical mold with a diameter of 1 cm, and the mold was left to stand for 48 hours.

[0227] After demoulding, a solid monolithic cylindrical material with a height of about 4 cm and a diameter of 1 cm was obtained.

[0228] The monolith was then washed with a 50:50 THF-acetone mixture in a Soxhlet extractor to remove dodecane and then dried at 80 °C.

[0229] After drying for 24 h, a solid and firm monolithic material was obtained which retained its dimensions ( Figure 2 ).

[0230] Example 1A .

[0231] In this example, a monolith similar to that of Example 1 but not comprising zeolite LTA submicron particles was prepared. The monolith was synthesized according to the same protocol as in Example 1 (referred to as Protocol P0).

[0232] Example 1B .

[0233] In this example, pure geopolymer (purely synthetic geopolymer) was prepared, ie according to protocol P0, but without using submicron zeolite and TTAB, and without adding oil to form an emulsion.

[0234] The obtained geopolymer has a mass of 71.3 m 2 .g -1 Specific surface area.

[0235] Example 1C .

[0236] In this example, the materials prepared in Examples 1, 1A, and 1B were characterized.

[0237] The internal structures of the two monoliths prepared in Example 1 and Example 1A were observed by scanning electron microscopy (SEM).

[0238] The images obtained are shown in Figure 3A and 3B middle.

[0239] Observe:

[0240] - In the absence of zeolite particles, the material has honeycomb-like pores with no (or little) interconnections.

[0241] - In the presence of zeolites, the microstructure of the material is completely different. The pores no longer have a honeycomb structure and their interconnection is enhanced.

[0242] The monoliths prepared in Examples 1 and 1A were analyzed by nitrogen adsorption-desorption to determine their specific surface area (BET model) and pore size distribution (<60 nm, BJH model).

[0243] For the geopolymer containing zeolite (material of Example 1) and not containing zeolite (material of Example 1A), 34.4 and 37.8 m 2 .g -1 Specific surface area.

[0244] Figure 4 The mesopore size distribution of both materials is shown.

[0245] The figure also shows the mesopore size distribution of the neat geopolymer prepared in Example 1B.

[0246] The synthesized pure geopolymer (Example 1B) and the material containing no zeolite prepared using protocol P0 (Example 1A) have a pore size distribution centered around 19-20 nm, while the material containing zeolite synthesized using protocol P0 (Example 1 according to the invention) has a pore size distribution centered around 27 nm.

[0247] Therefore, the presence of zeolite in the formulation can increase the size of the mesopores.

[0248] Fig.13 The adsorption isotherm of the pure geopolymer is shown. The isotherm has a type IV shape in the IUPAC classification, indicating the presence of micropores in the structure of the geopolymer (due to the shape of the curve at low pressure).

[0249] Then, the two monoliths prepared in Example 1 and Example 1A were ground into powders and then subjected to X-ray diffraction (XRD) analysis.

[0250] XRD analysis was also performed on pure submicron zeolite LTA powder.

[0251] The results of these analyses are shown in Figure 5 middle.

[0252] (Note: Figure 5 In the present invention, a "neat geopolymer" is mentioned: this is a geopolymer synthesized without using submicron zeolites and TTAB and without adding oil to form an emulsion (geopolymer of Example 1B)).

[0253] Figure 5 The three diffraction patterns shown in show that in the material prepared in Example 1 according to the present invention, submicron particles of zeolite LTA are indeed incorporated into the structure of the macroporous geopolymer.

[0254] Example 1D.

[0255] In this example, the effectiveness of the material prepared in Example 1 according to the present invention and the material prepared in Example 1A for purifying emissions containing strontium (Sr) was investigated.

[0256] In other words, in this example, the material prepared in Example 1 according to the present invention and the material prepared in Example 1A were tested in the case of application as Sr-adsorbing materials.

[0257] Therefore, Sr adsorption tests in solution were performed to verify that the zeolite LTA intercalated into the geopolymer framework in the material prepared in Example 1 was indeed active.

[0258] The parameter Kd (partition coefficient in mL / g) used to monitor strontium adsorption was calculated according to the following formula:

[0259] [Mathematical formula 1]

[0260]

[0261] in:

[0262] -[Sr] init and [Sr] fin represent the initial and final Sr concentrations in the solution (mg / L),

[0263] -V is the volume of the solution (mL),

[0264] -m is the material mass (g).

[0265] The protocol for the adsorption test is as follows:

[0266] - 50 mg of the material (in bulk form) was placed in 50 mL of a matrix (aqueous solution) containing 0.05 mol / L NaNO3, 50 ppm of Ca (added in the form of Ca(NO3)2), 2 ppm of Cs (added in the form of CsNO3) and 2 ppm of Sr (added in the form of Sr(NO3)2).

[0267] - The matrix with added materials was stirred for 24 h using a rotary stirrer.

[0268] - After stirring, 15 ml of the supernatant was extracted with a syringe, the sample was filtered with a 0.22 μm syringe filter, and then the residual Sr concentration was analyzed by inductively coupled plasma (ICP) spectroscopy.

[0269] • The geopolymer monolith without zeolite (Example 1A) had a Kd value of 1128 mL / g, whereas the geopolymer monolith containing zeolite LTA particles (Example 1 according to the invention) had a Kd value of 5024 mL / g.

[0270] The results show that the zeolite LTA particles incorporated into the macroporous geopolymer (according to Example 1 of the present invention) have a significantly improved purification efficiency, in fact a 5-fold improvement.

[0271] This result clearly shows that the zeolite particles can come into contact with polluted emissions.

[0272] Example 2.

[0273] In this example, monoliths comprising geopolymers incorporating submicron zeolites were prepared by various methods to investigate the effect of the preparation method on the macroporosity of the monolith.

[0274] Therefore, in order to observe the effect of the preparation method on the macroporosity and macroporous interconnectivity of the material, one or two additional steps, referred to as "UT" steps, were added to the different steps of Scheme P0 (referred to as steps 1, 2, 3, 4 and 5 ("UT") in Example 1).

[0275] Therefore three new regimens (referred to as regimens P1, P2 and P3) were tested and are described in Table 1 below.

[0276] The amounts of material added were similar to those used in Example 1. Therefore, the final materials obtained using protocols P0, P1, P2 and P3 had exactly the same final chemical composition.

[0277] [Table 1]

[0278] P1 P2 P3 1, 2, UT, 3, 4, UT 1, 2, UT, 3, UT, 4, UT 1, 2, 3, UT, 4, UT

[0279] Table 1 : Description of the different steps of solutions P1, P2 and P3 .

[0280] Importantly, the descriptions of schemes P0, P1, P2, P3 and P4 given here in the specific cases of Example 1 and Example 2 can be easily summarized and in particular the specific conditions of the different steps can be easily summarized with respect to the “Summary of the Invention” given above.

[0281] Regardless of the protocol used, the emulsion was systematically stabilized and then placed in a mold and left to stand for 48 h to allow the geopolymer skeleton to solidify and form a cylindrical monolith with a height of several centimeters and a diameter of 1 cm.

[0282] Dodecane was removed by washing with a 50:50 THF-acetone mixture in a Soxhlet extractor for 24 h and the monolith was dried at 80 °C for 24 h.

[0283] The internal structure of each obtained monolith was then observed by scanning electron microscopy (SEM).

[0284] The images obtained are shown in Fig. 6A ,6B and 6C.

[0285] Observe:

[0286] - Plan P1( Fig. 6A ) produces a so-called "honeycomb" material in which the pores appear to be slightly interconnected.

[0287] - Plan P2( Figure 6B ) produces an intermediate microstructure with cellular pore remnants and the presence of non-cellular and more interconnected pores.

[0288] - Plan P3( Figure 6C ) on its own produces mostly non-cellular and highly interconnected pores.

[0289] The monoliths were analyzed by nitrogen adsorption-desorption to determine their specific surface area (Brunauer, Emmett, and Teller model, “BET”) and their pore size distribution (<60 nm, Barrett, Joyner, Halenda model, “BJH”). 33.1, 30.6, and 31.5 m were measured for the materials prepared by protocols P1, P2, and P3, respectively. 2 .g -1 Specific surface area.

[0290] Figure 7 The pore size distribution (<60 nm) of the three materials is shown.

[0291] The pore size distribution of each material is centered at 27 nm, similar to the pore size distribution obtained for zeolite-containing materials synthesized using the P0 protocol.

[0292] Therefore, modifications of the synthetic protocol do not seem to have any effect on the mesopore size distribution.

[0293] Therefore, these results clearly demonstrate the impact of the inversion of the preparation steps on the macroporosity of the material and the interconnectivity of the macropores, without changing the mesoporosity of the walls.

[0294] These results show that plan P3 is the preferred plan, followed by plan P0, then plan P2, and finally plan P1.

[0295] Example 3.

[0296] In this example, the effect of the preparation method on the purification efficacy of a geopolymer monolith containing submicron zeolite LTA particles was investigated.

[0297] To this end, the effectiveness of materials prepared according to protocols P1, P2 and P3 for the purification of strontium-containing emissions was investigated.

[0298] A "batch" study similar to that performed in Example ID was performed.

[0299] Figure 8 Kd values ​​obtained for materials prepared using Protocols P1, P2 and P3 are shown.

[0300] Figure 8 Also shown are the Kd values ​​obtained with a geopolymer monolith not comprising zeolite (prepared in Example 1A according to protocol P0), with a Kd value of 1128 mL / g: see Example 1C) and with a geopolymer monolith containing zeolite LTA particles and prepared according to protocol P0 (according to Example 1 of the invention, with a Kd value of 5024 mL / g: see Example 1D).

[0301] exist Figure 8 In the , clear differences between the Kd values ​​are observed, which is due to the different internal porous microstructures of the materials giving the active zeolite particles more or less contact with the emissions to be purified.

[0302] therefore:

[0303] - The materials prepared according to protocols P0 and P3 have a non-cellular and more interconnected microstructure, which has higher Kd values.

[0304] - The material prepared according to protocol P1 has a highly cellular and less interconnected structure with a Kd value only twice greater than that of the material without zeolite.

[0305] - The material prepared according to protocol P2 has an intermediate microstructure and therefore yields an intermediate Kd value.

[0306] These results show that plan P3 is the preferred plan, followed by plan P0, then plan P2, and finally plan P1.

[0307] Example 4.

[0308] In this example, a monolith comprising a geopolymer incorporating micron-sized zeolites was prepared according to the present invention.

[0309] More precisely, in this example, according to the invention, micron particles of zeolite 4A, known to be an efficient and selective adsorbent of Sr in aqueous media, are incorporated into a macroporous geopolymer matrix.

[0310] Micronized particles of zeolite 4A are commercial particles manufactured by the company CTI (Céramiques Techniques Industrielles).

[0311] Fig. 9 SEM images of these particles are shown, with a size of 4 to 5 μm.

[0312] Using preparation protocol P3 (described in Example 2), the mass of submicron zeolite was replaced by an equal mass of micron zeolite.

[0313] A viscous emulsion is thus obtained at the end of the last step (step "UT") of protocol P3.

[0314] The viscous emulsion was placed in a mold and allowed to stand for 48 hours.

[0315] After demoulding, a monolithic material is obtained.

[0316] The monolith was then washed with a 50:50 THF-acetone mixture in a Soxhlet extractor to remove dodecane, and the material was then dried at 80 °C.

[0317] After drying for 24 h, a cylindrical monolith with a height of several centimeters and a diameter of 1 cm was obtained.

[0318] The monolithic material was then ground into powder and then subjected to X-ray diffraction (XRD) analysis.

[0319] Example 4A .

[0320] In this example, a monolith similar to Example 4 but without micron particles of zeolite 4A was prepared. The monolith was synthesized according to the same protocol as Example 4 (referred to as Protocol P3), but without the use of micron zeolite and TTAB and without the addition of oil to form an emulsion.

[0321] The monolithic material was then ground into powder and then subjected to X-ray diffraction (XRD) analysis.

[0322] Example 4B.

[0323] In this example, the powders obtained at the end of Examples 4 and 4A were subjected to X-ray diffraction (XRD) analysis.

[0324] XRD analysis was also performed on the micron zeolite 4A powder.

[0325] The results of these XRD analyses are shown in Fig.10 middle.

[0326] (Note: Fig.10 In the examples, a "pure geopolymer" is mentioned: this is a geopolymer synthesized without using micron zeolite and TTAB and without adding oil to form an emulsion (geopolymer of Example 4A)).

[0327] Fig.10 The three diffraction patterns shown in show that the micronized zeolite 4A particles have indeed been incorporated into the structure of the macroporous geopolymer.

[0328] Example 4C.

[0329] In this example, the effectiveness of the material prepared in Example 4 according to the present invention for purifying emissions containing strontium (Sr) was investigated.

[0330] To this end, a "batch" test similar to that performed in Example 1D was performed.

[0331] A Kd value of 5528 mL / g was obtained, which is greater than the Kd value of 1128 mL / g for a geopolymer without active particles (see Example ID), indicating the efficacy of the material.

[0332] Example 5.

[0333] In this example, a geopolymer monolith comprising incorporated nanocrystalline silicate titanate (CST) particles was prepared according to the present invention.

[0334] More precisely, in this example, according to the present invention, nanoparticles of crystalline silicate titanate (CST), known to be efficient and selective adsorbents of Sr in aqueous media, are incorporated into a macroporous geopolymer "skeleton" matrix.

[0335] Nano CST particles are commercial particles manufactured by UOP Corporation.

[0336] Fig.11 Laser particle size distribution analysis of these particles is shown, which shows that the size of these particles in solution after dispersion with ultrasound is about 10 to 20 nm.

[0337] Using preparation protocol P3 (described in Example 2), the mass of submicron zeolite was replaced by an equal mass of CST.

[0338] A viscous emulsion is thus obtained at the end of the last step (step "UT") of protocol P3.

[0339] The viscous emulsion was placed in a mold and allowed to stand for 48 hours.

[0340] After demoulding, a monolithic material is obtained.

[0341] The monolith was then washed with a 50:50 THF-acetone mixture in a Soxhlet extractor to remove dodecane, and the material was then dried at 80 °C.

[0342] After drying for 24 h, a cylindrical monolith with a height of several centimeters and a diameter of 1 cm was obtained.

[0343] The monolith is then ground into powder.

[0344] Example 5A .

[0345] In this example, a monolith similar to that of Example 5 but excluding nano CST particles was prepared. The monolith was synthesized according to the same protocol as in Example 5 (referred to as Protocol P3).

[0346] The monolith is then ground into powder form.

[0347] Example 5B.

[0348] In this example, X-ray diffraction (XRD) analysis was performed on the powders obtained at the end of Examples 5 and 5A.

[0349] XRD analysis of the nano-CST powders was also performed.

[0350] The results of these XRD analyses are shown in Fig.12 middle.

[0351] (Note: Fig.12 In the present invention, pure geopolymer is mentioned: this is a geopolymer synthesized without using CST and TTAB and without adding oil to form an emulsion (geopolymer of Example 4A)).

[0352] These three diffraction patterns indicate that the nano-CST particles have indeed been incorporated into the structure of the macroporous geopolymer.

[0353] Example 5C.

[0354] In this example, the effectiveness of the material prepared in Example 5 according to the present invention for purifying emissions containing strontium (Sr) was investigated.

[0355] To this end, a "batch" test similar to that performed in Example 1D was performed.

[0356] A Kd value of 4732 mL / g was obtained, which is greater than the Kd value of 1128 mL / g for a geopolymer without active particles (see Example ID), indicating the efficacy of the material.

[0357] References

[0358] [1]FR-A1-2791905.

[0359] [2] Didi Y., Said B., Cacciaguerra T., Nguyen KL, Wernert, V., Denoyel R., Co D., Sebai W., Belleville MP, Sanchez-Marcano J., Fajula F., Galarneau A., "Synthesis of binderless FAU-X(13X) monoliths with hierarchical porosity", Microporous and Mesoporous Materials, 281 (2019) 57-65.

[0360] [3] Said B., Cacciaguerra T., Tancert F., Fajula F., Galarneau A., "Sizecontrol of self-supported LTA zeolite nanoparticles monoliths", Microporous and Mesoporous Materials, 227 (2016) 176-190.

[0361] [4] WO-A1-2016 / 0382016.

[0362] [5] F. Liguori, P. Barbaro, B. Said, A. Galarneau, V. Dal Santo, E. Passaglia, A. Feis, "Unconventional Pd@Sulfonated Silica Monoliths Catalysts for Selective Partial Hydrogenation Reactions under Continuous Flow," Chemcatchem, 9 (2017) 3245-3258.

[0363] [6]FR-A-3035660

[0364] [7]FR-A1-3037583.

[0365] [8]FR-A1-3015476

[0366] [9]WO-A1-2012 / 049412.

Claims

1. A solid material having open, multiple and at least partially interconnected pores, said solid material comprising a matrix formed of a microporous-mesoporous geopolymer and particles of at least one solid compound different from said geopolymer, said matrix having at least partially interconnected open macropores surrounded by sides or walls formed of microporous-mesoporous geopolymer, said particles being distributed in said macropores and / or in said sides or walls, said particles of at least one solid compound different from said geopolymer are active particles, said active particles being able to act in a chemical, physical or physicochemical process, The active particles are selected from the group consisting of particles of at least one solid metal cation exchanger compound, catalyst particles and adsorbent compound particles.

2. The solid material according to claim 1, which is in the form of particles; or in the form of a monolith.

3. The solid material according to claim 1 or 2, wherein The particles of the at least one solid compound different from the geopolymer have an average size ranging from 2 nanometers to 100 micrometers.

4. The solid material according to claim 3, wherein The particles of at least one solid compound different from the geopolymer are selected from the group consisting of nanoparticles, submicron particles and micron particles.

5. The solid material according to claim 1, wherein The solid metal cation exchanger compound is selected from the group consisting of: zeolites; alkaline titanosilicates; coordination polymer particles and mixtures thereof.

6. The solid material according to claim 1 or 2, wherein: The amount of particles of at least one solid compound different from the geopolymer is between 0.1 and 30% by mass of the total mass of the solid material.

7. A method for preparing a solid material according to any one of claims 1 to 6, the method comprising at least the following steps: a) preparing an oil-in-water emulsion by mechanically agitating a mixture comprising an oil phase and an aqueous phase with shear, said oil-in-water emulsion being formed by droplets of said oil phase dispersed in a continuous aqueous phase, and particles of at least one solid compound, said aqueous phase comprising an activation solution, a source of aluminosilicates capable of forming a geopolymer by dissolution / polycondensation and optionally a surfactant, said particles being present at the interface formed by said continuous aqueous phase of said emulsion and the droplets of said oil phase dispersed in said continuous aqueous phase, said activation solution being an aqueous solution with a pH value greater than 9; b) allowing the emulsion to stand and be shaped to obtain a selected size and shape and to form the geopolymer matrix by polycondensation; c) removing the oil phase, thereby obtaining the solid material according to any one of claims 1 to 6.

8. The method according to claim 7, wherein: The oil phase of the mixture consists of one or more straight-chain or branched alkanes having 7 to 22 carbon atoms.

9. The method according to claim 7 or 8, wherein: Prior to step a), the following sub-steps a1) to a4) are performed to prepare the mixture comprising an oil phase and an aqueous phase: a1) preparing an aqueous suspension of particles of at least one solid compound in water or in an aqueous solution comprising a surfactant; a2) adding an oily phase to said aqueous suspension obtained at the end of step a1), thereby obtaining a biphasic mixture comprising said oily phase and an aqueous phase consisting of said aqueous suspension; a3) adding an aqueous solution having a pH value greater than 9 to the aqueous phase of the biphasic mixture obtained at the end of step a2); a4) adding a source of aluminosilicate capable of forming said geopolymer by dissolution / polycondensation to the aqueous phase of said biphasic mixture obtained at the end of step a3).

10. The method according to claim 9, wherein: After step a2) and before step a3), the two-phase mixture comprising the oil phase and the aqueous phase consisting of the aqueous suspension is subjected to mechanical stirring with shear; and / or after step a3) and before step a4), the two-phase mixture is subjected to mechanical stirring with shear.

11. Use of the solid material according to any one of claims 1 to 6 for catalyzing a chemical reaction, for filtering a fluid, or for separating or extracting a substance contained in a fluid.

12. A method for separating at least one metal cation or metalloid cation from a liquid medium containing the same, wherein: The liquid medium is brought into contact with the solid material according to any one of claims 1 to 6.

13. The method according to claim 12, wherein: The liquid medium is an aqueous liquid medium.

14. The method according to claim 12 or 13, wherein: The liquid medium is selected from liquids and effluents from the nuclear industry and from installations and processes using radionuclides.

15. The method according to claim 12 or 13, wherein: The cation concentration is 0.1 pg to 500 mg / L.

16. The method according to claim 12 or 13, wherein: The cation is selected from alkali metals, alkaline earth metals, transition metals, heavy metals, rare earth elements, actinides, noble gases, and isotopes thereof.

17. The method according to claim 12 or 13, wherein: The cation is selected from the group consisting of Sr, Cs, Co, Ag, Ru, Fe, Tl, and radioactive isotopes thereof.

18. The method according to claim 17, wherein: The cation is 134 Cs, or 137 Cs, or 90 Sr cation.

Citation Information

Patent Citations

  • Porous geopolymer materials

    US20130055924A1